Exploring Early Gesture and Language Development Trends in Sesotho-Speaking Infants (8 to 18 Months) - Du Plessis, Tristan Reece (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.